Crashworthiness analysis of the structure of metro vehicles constructed from typical materials and the lumped parameter model of frontal impact - Zhu, Tao; Xiao, Shou-Ne; Hu, Guang-Zhong; Yang, Guang-Wu; Yang, Chao (Transport, 2019)
This paper establishes a Finite Element (FE) model of a rigid barrier impact of a single vehicle constructed from carbon steel, stainless steel, and aluminum alloy, which are three typical materials used in metro vehicle car body structures. The different responses of the three materials during the collision are compared. According to the energy absorption, velocity, deformation and collision force flow characteristics of each vehicle, the relationship between the energy absorption ratio of the vehicle body and the energy absorption ratio of its key components is proposed. Based on the collision force flow distribution proportion of each component, the causes of the key components’ deformation are analysed in detail. The internal relationship between the deformation, energy absorption and impact force of the key components involved in a car body collision is elucidated. By determining the characteristic parameters describing the vehicle’s dynamic stiffness, a metro vehicle frontal impact model using lumped parameters is established that provides a simple and efficient conceptual design method for railway train safety design. These research results can be used to guide the design of railway trains for structural crashworthiness.